Di antara Dua Peran: R. Moch Machin Kepala Penghulu dan Bupati Kediri (1942-1960) - Anggraeni, Shofi Dian; Afiyanto, Hendra (Historia Madania: Jurnal Ilmu Sejarah, 2023)
The institutions of kepenghuluan has been established over a long time, during the Dutch East Indies the informal  institution of kepenghuluan  was found in several regions, one of which was in Kediri district. One of the figures of head of Kediri R. Moch. Machin, was the  youngest head of the Dutch East Indies, who was appointed at the age of 30. In the seventh year of his leadership as head of the district, R. Moch. Machin was become as regent of Kediri in an emergency situation ahead of the second military aggression launched by the Dutch. In this research, there are two problem formulations: first, what is the background of the appointment of R. Moch. Machin as the young head  penghulu of Kediri? Second, how was R. Moch. Machin finally appointed as regent of Kediri? This research aims to find out how  R. Moch. Machin  become the young head penghulu of Kediri, and later served as regent of Kediri, as well as how R. Moch. Machin's achievements in his role as chief penghulu and regent of Kediri. This research uses a socio-historical approach that includes heuristics, verification, interpretation, and histsriography stages. Some of the findings in this research include: first, the inauguration of R. Moch. Machin as the youngest head of the Dutch East Indies was published in the Bataviasch Nieuwsblaad newspaper. Second, the appointment of R. Moch. Machin as replacement regent was based on deliberations from the kiai and direct advice from Ir. Sukarno. Thirdly, R. Moch. Machin’s contributions as regent of Kediri, among other things, carried out repairs to infrastructure and residents' houses due to the Dutch military attack and founded the Kediri 'PERSIK' football club.